Acute exercise increases the expression of KIR2DS4 by promoter demethylation in NK cells - Schenk, Alexander; Zimmer, Philipp (International journal of sports medicine, 2019)
Positive effects of exercise on cancer prevention and progression have been proposed to be mediated by stimulating natural killer (NK) cells. Because NK cell receptors are regulated by epigenetic modifications, we investigated whether acute aerobic exercise and training change promoter DNA methylation and gene expression of the activating KIR2DS4 and the inhibiting KIR3DL1 gene. Sixteen healthy women (50-60 years) performed a graded exercise test (GXT) and were randomized into either a passive control group or an intervention group performing a four-week endurance exercise intervention. Blood samples (pre-, post-GXT and post-training) were used for isolation of DNA/RNA of NK cells to assess DNA promoter methylation by targeted deep-amplicon sequencing and gene expression by qRT-PCR. Potential changes in NK cell subsets were determined by flow cytometry. Acute and chronic exercise did not provoke significant alterations of NK cell proportions. Promoter methylation decreased and gene expression increased for KIR2DS4 after acute exercise. A high gene expression correlated with a low methylation of CpGs that were altered by acute exercise. Chronic exercise resulted in a minor decrease of DNA methylation and did not alter gene expression. Acute exercise provokes epigenetic modifications, affecting the balance between the activating KIR2DS4 and the inhibiting KIR3DL1, with potential benefits on NK cell function.
Published online: 3.12.2018
Gesehen am 07.08.2019